Exposure to endocrine-disrupting compounds such as phthalates and bisphenol A is associated with an increased risk for obesity. Issue 5 (September 2021) - Biemann, Ronald; Blüher, Matthias; Isermann, Berend
Abstract : Increasing evidence from epidemiological, animal and in vitro studies suggests that the increased production of synthetic chemicals that interfere with the proper functioning of the hormonal system, so-called endocrine-disrupting compounds (EDCs), might be involved in the development and rapid spread of obesity, coined the obesity epidemic. Recent findings have demonstrated that EDCs may interfere with hormonal receptors that regulate adipogenesis and metabolic pathways. Furthermore, prenatal exposure to EDCs has been shown to influence the metabolism of the developing embryo through epigenetic mechanisms and to promote obesity in subsequent generations. In this Review, we discuss the potential impact of bisphenol A (BPA) and phthalate-based plasticizers on obesity and obesity-related metabolic disorders. Special emphasis is given to the obesogenic effects of prenatal exposure and strategies for identifying, regulating, and replacing EDCs.